Tourism potential of the Belarusian province (sociological analysis) - A. Yu. Sakovich (Вестник Майкопского государственного технологического университета, 2025)
Introduction. In the Republic of Belarus special attention is paid to the development of the tourism potential of provincial regions. This is due to the fact that, on the one hand, they have large recreational resources, on the other hand, they are in a vulnerable position due to their remoteness from the capital and large cities. Therefore, the purpose of the research is to study the tourism potential of the Belarusian province.Materials and methods. A typical example of a provincial recreational region of the Republic of Belarus is the Myadel district. In this regard, in July-August 2024, in-depth interviews with tourists renting farmsteads on the shores of (near) lakes in the studied region were organized. The sample population of the study was 12 people.The Research results. The survey results have shown that the Belarusian province attracts travelers with its cleanliness, tidiness, natural beauty, and tranquility. Respondents were satisfied with their vacation in the Myadel district. Characterizing the living conditions of the rented farmstead, they emphasized the price-quality ratio. As a rule, the respondents received the housing they expected. It has been found that the social infrastructure of the resort village of Naroch and the city of Myadel is most adapted to the needs of tourists. However, the recreational zone of the region is much wider and requires the construction of canteens/cafes/bars, equipped beaches, sports grounds for adults, specialized areas for children in all popular tourist settlements of the Myadel region.Discussion and conclusion. Investments are needed for the development of the region. The results of the study can be used in the development of investment projects aimed at improving the social infrastructure of popular tourist settlements.